Enhancing productivity: the role of management practices - Siebers, Peer-Olaf; Aickelin, Uwe; Battisti, Giuliana; Celia, Helen; Clegg, Chris; Fu, Xiaolan; Hoyos, Raphael De; Iona, Alfonsiana; Petrescu, Alina; Peixoto, Adriano (Advanced Institute of Management Research, 2008)
There is no doubt that management practices are linked to the productivity and performance of a company. However, research findings are mixed. This paper provides a multi-disciplinary review of the current evidence of such a relationship and offers suggestions for further exploration. We provide an extensive review of the literature in terms of research findings from studies that have been trying to measure and understand the impact that individual management practices and clusters of management practices have on productivity at different levels of analysis. We focus our review on Operations Management (OM) and Human Resource Management (HRM) practices as well as joint applications of these practices. In conclusion, we can say that taken as a whole, the research findings are equivocal. Some studies have found a positive relationship between the adoption of management practices and productivity, some negative and some no association whatsoever. We believe that the lack of universal consensus on the effect of the adoption of complementary management practices might be driven either by measurement issues or by the level of analysis. Consequently, there is a need for further research. In particular, for a multi-level approach from the lowest possible level of aggregation up to the firm-level of analysis in order to assess the impact of management practices upon the productivity of firms.